Assessment by bioeconomic modeling water price scenarios of the resilience of agricultural production systems in a semi-arid region: Case of Baalbeck El Hermel – Lebanon - Al fakih, Ahmad; Darwich, Salem; Madau, Fabio (Technium Sustainability, 2024)
Baalbeck El Hermel Governorate, particularly the semi-arid region is increasingly threatened by climate change. These disturbances, more specifically, concerning the limit in water resources generate problems for the agricultural systems constituting the principle source of families’ subsistence in this zone. This study was established to evaluate, via a bioeconomic modeling approach, the resilience of agricultural systems in Baalbeck El Hermel and perceive their adaptation techniques under conditions of water scarcity. In this context, we have selected three typical farms representative of the driest northern zone receiving the least precipitation. Several behaviors and levels of resilience of these farms were showed after analysis of the results: 1) farms specializing in market gardening or perennial crops are very sensitive to drought conditions and are not resilient in the face of water limit conditions; 2) the diversified farm with olive tree dominance is less sensitive and more resilient. The analysis of the water pricing scenario showed an improvement in water management but a limit in the adaptive capacity of farmers, hence the necessity to adapt resilience-building strategies for the targeted zone.